2013
DOI: 10.1038/nature12599
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cells as a site of origin for intestinal inflammation

Abstract: Autophagy related 16-like 1 (ATG16L1) as a genetic risk factor has exposed the critical role of autophagy in Crohn’s disease (CD)1. Homozygosity for the highly prevalent ATG16L1 risk allele, or murine hypomorphic (HM) activity causes Paneth cell dysfunction2,3. As Atg16l1HM mice do not develop spontaneous intestinal inflammation, the mechanism(s) by which ATG16L1 contributes to disease remains obscure. Deletion of the unfolded protein response (UPR) transcription factor X-box binding protein-1 (Xbp1) in intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
704
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 641 publications
(728 citation statements)
references
References 51 publications
(85 reference statements)
21
704
1
2
Order By: Relevance
“…In addition, mice defective in ER stress signalling or autophagy, such as XBP1 IEC-KO mice 36 and hypomorphic ATG16L1 mice 37 , respectively, display Paneth cell abnormalities. Moreover, intestinal inflammation may even emerge from malfunctioning Paneth cells 38 . A20 deficiency in IECs does not cause spontaneous Paneth cell defects, but sensitizes their apoptotic loss in inflammatory conditions, either by direct low-dose TNF exposure or by exposure to cytokines produced by hyperactive A20-deficient myeloid cells, including TNF and IFNg.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mice defective in ER stress signalling or autophagy, such as XBP1 IEC-KO mice 36 and hypomorphic ATG16L1 mice 37 , respectively, display Paneth cell abnormalities. Moreover, intestinal inflammation may even emerge from malfunctioning Paneth cells 38 . A20 deficiency in IECs does not cause spontaneous Paneth cell defects, but sensitizes their apoptotic loss in inflammatory conditions, either by direct low-dose TNF exposure or by exposure to cytokines produced by hyperactive A20-deficient myeloid cells, including TNF and IFNg.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, failure to remove ER stress-induced responses in mice with genetic deficiencies in either Atg16l1 or Atg7 causes a severe spontaneous Crohn disease-like transmural ileitis through NFKB (nuclear factor of kappa light polypeptide gene enhancer in B-cells 1) activation and TNF signaling. 108 It should be noted, however, that pharmacological autophagy inhibition (e.g., by 3-methyladenine) could not always confirm the above-described autophagy-mediated effects, with 3-methyladenine being reported to both induce and decrease toll-like receptor-mediated TNF secretion. 83,109 These conflicting data should encourage more careful investigations using both genetic and pharmacological inhibition, as discrepancies may result from off-target or at least autophagyindependent inhibitory effects linked to the chosen inhibition strategy.…”
Section: Atg16l1-dependent Signaling In Crohn Diseasementioning
confidence: 99%
“…107 Moreover, a recent study reported a crucial interaction between ER stress and autophagy among the inflamed Paneth cells of the intestinal epithelium. 108 Impairment of the unfolded protein response by deleting its key transcription factor, Xbp1, or secondary to deficiency in the autophagic functions due to the genetic removal of Atg16l1 or Atg7 in intestinal epithelial cells, results in antagonistic compensatory engagement; 108 the induction of ER stress in Xbp1 knockout mice triggers the activation of a compensatory autophagic response and the formation of autophagosomes in Paneth cells. Accordingly, failure to remove ER stress-induced responses in mice with genetic deficiencies in either Atg16l1 or Atg7 causes a severe spontaneous Crohn disease-like transmural ileitis through NFKB (nuclear factor of kappa light polypeptide gene enhancer in B-cells 1) activation and TNF signaling.…”
Section: Atg16l1-dependent Signaling In Crohn Diseasementioning
confidence: 99%
“…Also, Blumberg et al has shown that XBP1, a transcription factor that is induced upon ER stress, is another susceptibility gene that leads to Paneth cell dysfunction [60]. By combining functional deletion of both ATG16L1 and XBP1 in mice models, they identified that ileal CD may arise solely from Paneth cell dysfunction [61]. Another study has shown that in Crohn's disease, a Paneth cell-specific cell death is promoted by a mechanism called ''Necroptosis'' [62].…”
Section: Role Of Iecs In the Pathogenesis Of Ibdmentioning
confidence: 99%